Adaptabilidade e estabilidade para caracteres agronômicos em clones de batata resistentes ao Potato Virus Y (PVY) - Andrade, Mario Henrique Murad Leite (2016)
The phenotype of an individual is the sum of its genotype and the environment influence. Performed the observation of the same individual in various environments there will be different manifestations of the phenotype, due to the genotype interaction with the environment. This interaction makes difficult the breeders job once the ranking of genotypes is modified from one environment to the other, due to the lack of a perfect correlation between genotype and phenotype. The genotype by environment interaction is a reality in the daily lives of breeders and farmers. It is one of the biggest obstacles in breeding programs because the genotypic values, when the presence of the interaction is ignored, could be overestimated or underestimated, reducing the gain with selection. The aim of this study was to evaluate the adaptability and stability of potato clones (MLG) resistant to Potato Virus Y for growing conditions and climate of the southern state of Minas Gerais. Six tests were carried out using 18 clones of potato breeding program of UFLA and four cultivars usually planted in the state, using the randomized complete block design with three replications. We evaluate stability of agronomical characters like total production of large tubers, specific weight and general appearance of tubers. From the analysis of variance was detected strong interaction between the varieties used and the different planting environments and the interaction explained most of the variation. Given the interaction we proceeded to stability analysis using the GGE Biplot method to improve understanding of the interrelationship between genotypes and environments. It was verified that some environments have similar results, being grouped in mega environments. The MLG clones used were more productive and adapted when compared to control. Highlighting the MLG-01-02, MLG-01-06, MLG-11-05 and MLG-23-37, which meet the requirements of table and pre-fried segments.